Employee commitment in context: The nature and implication of commitment profiles - Meyer, John; Stanley, L.; Parfyonova, N. (Academic Press, 2012)
It is well established that employee commitment can take different forms (e.g., affective, normative, and continuance), yet it is only recently that theory has been advanced to explain how these different forms combine to influence behavior (Meyer & Herscovitch, 2001). We tested this theory with data from employees in three human services organizations (N = 403). Using latent profile analyses, we identified six distinct profile groups and found that they differed on measures of need satisfaction, regulation, affect, engagement, organizational citizenship behavior, and well-being. The observed differences are consistent with the notion that a commitment profile provides a context that determines how the individual components are experienced (Gellatly, Meyer, & Luchak, 2006). We discuss the theoretical and practical implications of this context effect.